Brainstem encoding of speech and musical stimuli in congenital amusia: evidence from Cantonese speakers - Liu, Fang; Maggu, Akshay R.; Lau, Joseph C. Y.; Wong, Patrick C. M. (Frontiers in Human Neuroscience, 2015)
Congenital amusia is a neurodevelopmental disorder of musical processing that also impacts subtle aspects of speech processing. It remains debated at what stage(s) of auditory processing deficits in amusia arise. In this study, we investigated whether amusia originates from impaired subcortical encoding of speech (in quiet and noise) and musical sounds in the brainstem. Fourteen Cantonese-speaking amusics and 14 matched controls passively listened to six Cantonese lexical tones in quiet, two Cantonese tones in noise (signal-to-noise ratios at 0 and 20 dB), and two cello tones in quiet while their frequency-following responses (FFRs) to these tones were recorded. All participants also completed a behavioral lexical tone identification task. The results indicated normal brainstem encoding of pitch in speech (in quiet and noise) and musical stimuli in amusics relative to controls, as measured by FFR pitch strength, pitch error, and stimulus-to-response correlation. There was also no group difference in neural conduction time or FFR amplitudes. Both groups demonstrated better FFRs to speech (in quiet and noise) than to musical stimuli. However, a significant group difference was observed for tone identification, with amusics showing significantly lower accuracy than controls. Analysis of the tone confusion matrices suggested that amusics were more likely than controls to confuse between tones that shared similar acoustic features. Interestingly, this deficit in lexical tone identification was not coupled with brainstem abnormality for either speech or musical stimuli. Together, our results suggest that the amusic brainstem is not functioning abnormally, although higher-order linguistic pitch processing is impaired in amusia. This finding has significant implications for theories of central auditory processing, requiring further investigations into how different stages of auditory processing interact in the human brain.